تکنیک، عوارض و اثربخشی روش ترکیبی اپیدورال و اسپاینال در بی دردی زایمان: مرور سیستماتیک مطالعات کارآزمایی بالینی تصادفی آینده نگر - moardi, danial; fotohi, parviz; hesami, darya (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2025)
Abstract Introduction: According to World Health Organization guidelines, one of the most important components of maternity care in normal vaginal delivery is maternal satisfaction and comfort. Based on this principle, the present study was conducted as a systematic review of prospective randomized clinical trials to evaluate the technique, complications, and effectiveness of combined spinal–epidural (CSE) analgesia for labor. Materials and Methods: This systematic review included all scientific articles published in English over the past 20 years. A systematic search was performed in eight databases. Keywords were selected by two members of the research team based on prior reviews, the relevant literature, and controlled vocabularies from MeSH, Emtree, and other thesauri. Study quality was screened using the Newcastle–Ottawa/PRISMA-based checklist by three researchers. Results: After screening, 8 randomized clinical trials with a total sample size of 470 patients receiving combined spinal–epidural anesthesia were included. Common inclusion criteria were willingness for analgesia, absence of contraindications to neuraxial anesthesia, good physical health and ASA class I or II, cervical dilation of 3 cm, term pregnancy, and age over 18 years. Exclusion criteria were severe hemodynamic instability, local anesthetic toxicity, and high-risk pregnancy disorders. The procedure was generally performed at the L2–L4 levels, using 2.5 mg intrathecal bupivacaine with 15 µg fentanyl, followed by a 10 mL bolus of 0.1% bupivacaine with 2 µg/mL fentanyl into the epidural space. The most common adverse effect was pruritus. Across all studies, patients reported high satisfaction with pain relief. Advantages of this technique included rapid onset of analgesia, shortened labor stages, absence of motor block, and high maternal satisfaction. Conclusion: The combined spinal–epidural technique improves the quality of labor analgesia with fewer side effects. Further research is recommended to compare this technique with other methods of labor analgesia, using larger sample sizes and newer drugs with fewer adverse effects such as levobupivacaine and alpha-agonists. مقدمه: براساس دستورالعمل سازمان بهداشت جهانی یکی از مهمترین شیوه‌های مراقبت‌های بهداشتی در زایمان طبیعی، رضایت و آسایش مادر می‌باشد، بر این اساس مطالعه با هدف بررسی تکنیک، عوارض و اثربخشی روش ترکیبی اپیدورال و اسپاینال در بی‌دردی زایمان به شیوه مرور سیستماتیک مطالعات کارآزمایی بالینی تصادفی آینده‌نگر انجام شد. متدولوژی: پژوهش مرور نظام‌مند با جامعه مروری شامل تمام مقالات علمی منتشر شده به زبان انگلیسی در ٢٠ سال اخیر می‌باشد جستجوی مقالات به صورت سیستماتیک در ٨ پایگاه‌ داده انجام گردید. کلمات کلیدی توسط دو نفر از اعضای تیم پژوهش بر اساس بررسی‌های قبلی و ادبیات حوزه مطالعه و براساس دیتابیس های Mesh، Emtree و Thesauruses تعیین شد. غربالگری کیفیت مطالعات براساس چک لیست نیوکاسل-اتاوا PRISMA توسط ٣ نفر از اعضای تیم پژوهش انجام شد. یافته ها: پس از غربالگری، 8 مطالعه کارآزمایی بالینی با حجم نمونه 470 بیمار تحت بیحسی ترکیبی انتخاب شدند. معیارهای ورود مشترک، رضایت بی دردی، عدم منع بیحسی ، سلامت‌جسمی و کلاس ١یا٢ بیهوشی، اتساع دهانه رحم ٣ سانتیمتر، ترم بودن جنین، سن بالای ١٨سال بودند. معیار خروج اختلالات همودینامیک شدید، مسمومیت بیحس‌کننده‌ها، اختلالات پرخطر حاملگی بودند. روش اجرای پروسیجر درسطح بیحسی٢ تا ٤ لومبار و دریافت بوپیواکائین ٢.٥ میلی‌گرم با فنتانیل ١٥ میکروگرم داخل نخاعی، یک دوز بلوس ١٠ میلی‌لیتری بوپیواکائین %١/٠ با فنتانیل 2 میکروگرم در فضای اپیدورال بود. از عوارض شایع آن خارش بود. در تمامی مطالعات بیماران، رضایت بخشی از تسکین درد بالایی داشتند از مزایای این روش، شروع بی‌دردی سریع، کوتاه شدن مراحل زایمان، عدم بلوک حرکتی می باشد نتیجه گیری: روش ترکیبی اسپاینال و اپیدورال موجب افزایش کیفیت بیدردی زایمان با عوارض کمتر می‌گردد. پیشنهاد می‌شود پژوهش‌های بیشتری در مقایسه تکنیک با سایر روش‌های بی‌دردی و جامعه آماری بیشتر و استفاده از داروهای با عوارض کمتر مانند لووبوپیواکائین، آگونیست های آلفا انجام گردد.